2015
DOI: 10.1038/ncomms9435
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced light absorption by mixed source black and brown carbon particles in UK winter

Abstract: Black carbon (BC) and light-absorbing organic carbon (brown carbon, BrC) play key roles in warming the atmosphere, but the magnitude of their effects remains highly uncertain. Theoretical modelling and laboratory experiments demonstrate that coatings on BC can enhance BC's light absorption, therefore many climate models simply assume enhanced BC absorption by a factor of ∼1.5. However, recent field observations show negligible absorption enhancement, implying models may overestimate BC's warming. Here we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
297
7

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 314 publications
(331 citation statements)
references
References 60 publications
27
297
7
Order By: Relevance
“…MAC, a key parameter in our understanding of the net BC climate impact, is indeed a more relevant quantity to examine. A fast MAC enhancement in polluted environments as the BC gets coated with organic and inorganic species is consistent with recent findings (2,3 Coating of BC by soluble species not only enhances absorption of solar radiation but also reduces the BC atmospheric lifetime (7). Fig.…”
supporting
confidence: 75%
“…MAC, a key parameter in our understanding of the net BC climate impact, is indeed a more relevant quantity to examine. A fast MAC enhancement in polluted environments as the BC gets coated with organic and inorganic species is consistent with recent findings (2,3 Coating of BC by soluble species not only enhances absorption of solar radiation but also reduces the BC atmospheric lifetime (7). Fig.…”
supporting
confidence: 75%
“…A complex mixture of gas-phase organic compounds with a wide range of volatilities and molecular structures are co-emitted with BC from vehicles, contributing prominently to the urban SOA burden (Gentner et al, 2017, and references therein). Although it is not straightforward to identify the role of individual SOA precursors, previous studies have shown that organic coating thickness of BC particles and their degree of oxygenation increased with photochemical age or oxidant levels in the atmosphere (Cappa et al, 2012;Liu et al, 2015;Wang et al, 2017). Of particular concern is the timescale that is required for sufficient SOA condensation to modify the physical, chemical, and optical properties of BC near emission sources.…”
Section: Introductionmentioning
confidence: 99%
“…Real-time and mass-based chemical compositions of organic coatings on ambient BC particles were seldom reported until the recent development of an Aerodyne soot-particle aerosol mass spectrometer (SP-AMS; Cappa et al, 2012;Massoli et al, 2012Massoli et al, , 2015Onasch et al, 2012;Liu et al, 2015;Lee et al, 2016;Willis et al, 2016). In this study, we investigate formation of organic coatings on BC particles by deploying a SP-AMS in Fontana, California, which is located in the broader South Coast Air Basin and includes the greater Los Angeles area.…”
Section: Introductionmentioning
confidence: 99%
“…In the atmosphere, fractal soot aggregates age rapidly upon exposure to condensable vapors of sulfuric acid and oxidized organics [37][38][39][40][41][42]. Sufficiently aged soot may undergo significant structural changes, making the aggregates less fractal [16].…”
Section: Soot Aggregatesmentioning
confidence: 99%